An Innovative Aswaja Learning Model for Developing Theological Awareness among Madrasah Students - Ummu Qurratu Aini; Asriana Kibtiyah (Journal Of Islamic Education And Pesantren, 2024)
This article aims to analyze an innovative learning model of Ahlussunnah Wal Jama’ah (Aswaja) education in fostering theological awareness among madrasah students. The study is motivated by an empirical problem indicating that the teaching of Islamic creed in madrasahs often remains normative and transmissive, resulting in students’ understanding of Aswaja being largely memorization-based rather than reflective and contextual. This research employs a qualitative approach with a case study design to explore the dynamics of Aswaja learning practices in a madrasah context. Data were collected through in-depth interviews with teachers and students, classroom observations, and documentation analysis. The collected data were analyzed thematically using source and method triangulation to ensure the validity and credibility of the findings. The results reveal that an innovative Aswaja learning model integrating interactive lectures, active debates, inquiry-based learning, and the habituation of religious practices effectively promotes students’ theological awareness in an integrative manner. Such awareness develops through cognitive engagement in understanding theological arguments and differences among Islamic schools of thought, affective engagement in internalizing the values of tawassuth (moderation), tawazun (balance), and tasamuh (tolerance), and practical engagement through the rationalized practice of religious rituals. The findings indicate that Aswaja education functions not merely as a transmission of religious tradition but also as a reflective process of constructing moderate theological identity. This study highlights that pedagogical innovation in Aswaja learning holds strategic relevance for strengthening religious moderation within madrasah education.